Pengaruh Motivasi Mengikuti Pendidikan Teologi Terhadap Komitmen Mahasiswa Teologi Untuk Menjadi Pendeta - Claartje Pattinama (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to measure the influence of students' motivation in following theological education and their commitment to become pastors. This research is a quantitative study using the Structural Equation Model (SEM) to measure and analyze data obtained from questionnaires distributed to students. The research subjects were students of the Theology Faculty - UKIM. The results showed that: there was a positive and significant influence on the students' motivation in following theology education and their commitment to be pastors in the congregation. This concludes that with a strong student motivation in following theological education, then his commitment to become a pastor is a great opportunity. Thus it can be shown that there is hope for students that when they graduate, they can develop their theological education in accordance with their commitment to become pastors in the congregation.